THE EFFECT OF CALISTHENIC EXERCISE ON LEG EXPLOSIVE POWER - Ricardo, William; Kumaidah, Endang; Adji, Raden Mas Soerjo; Adyaksa, Gana (Faculty of Medicine, Diponegoro University, 2023)
Background: Physical fitness is a condition where the human body is able to perform daily activities without experiencing excessive fatigue. Physical exercise is one way to achieve physical fitness. Calisthenics is one of the strength exercises that utilize body weight as resistance to increase muscle strength. Previous research has shown that strength training can increase the explosive power of leg muscles measured through vertical jumps.Objective: Knowing the effect of calisthenic exercises on the explosive power of the leg muscles.Methods: Experimental research with quasi experimental design and methods of pre-test and post-test nonequivalent control group. The subjects were 37 active students of Diponegoro University, Semarang who were selected by purposive sampling and grouped into two groups. The control group without treatment (n=19), and the treatment group (n=18) were given calisthenic exercises for 6 weeks. The explosive power of the limb muscles was measured before and after the intervention with the vertical jump instrument and expressed as the vertical jump score (VJ score).Results: The results showed a significant increase in VJ score (p=0.030) in the treatment group compared to the control group. There was also a significant increase in VJ score (p<0.001) before and after the intervention in the treatment group.Conclusion: Calisthenic exercises for 6 weeks can increase muscle explosive power in the young adult age group.